1991
DOI: 10.1017/s0022215100117360
|View full text |Cite
|
Sign up to set email alerts
|

Lateral pharyngeal diverticulum

Abstract: We report a case of a lateral pharyngeal diverticulum arising from the right vallecula. The aetiology and clinical features of these rare lesions are discussed. Diagnosis, which is difficult clinically, was made by barium swallow examination of the pharynx. The importance of contrast radiology in the investigation of pharyngeal symptoms is emphasized by this case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…cr scans, however, were not routinely performed in these cases. Pace-Balzan et al 7 reported three patients presenting with sinonasal disease that were found to have clinical evidence of atrophic rhinitis. cr scans were performed in these patients and the results summarized as follows: 1) bony resorption and mucosal atrophy of inferior and middle turbinates; 2) nasal cavity enlargement with erosion and bowing of the lateral nasal wall; 3) hypoplasia of the maxillary sinuses; 4) bony resorption of the ethmoid complex with subsequent loss of definition of the ostiomeatal complex and 5) mucosal thickening in the paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…cr scans, however, were not routinely performed in these cases. Pace-Balzan et al 7 reported three patients presenting with sinonasal disease that were found to have clinical evidence of atrophic rhinitis. cr scans were performed in these patients and the results summarized as follows: 1) bony resorption and mucosal atrophy of inferior and middle turbinates; 2) nasal cavity enlargement with erosion and bowing of the lateral nasal wall; 3) hypoplasia of the maxillary sinuses; 4) bony resorption of the ethmoid complex with subsequent loss of definition of the ostiomeatal complex and 5) mucosal thickening in the paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…Vallecular diverticula, as opposed to Zenker’s diverticula, are a rare cause of dysphagia 1 . They may be a remnant of the second branchial cleft involving the thyrohyoid membrane between the middle and inferior constrictor muscles 2 …”
Section: Introductionmentioning
confidence: 99%